Misdiagnosis Overview by Mental Health Professionals in Malaysia and Indonesia - Ella Suzanna; Aziyah Binti Pehin Dato Hj Yaakub; Nurul Izzah Binti Shari (Jurnal Psikologi Terapan, 2018)
The purpose of this paper to look at how and why misdiagnosis happen among the psychiatrists or psychologists in Malaysia and Indonesia today and what made them changed their earlier diagnosis.  This study also aims to find out if  these Muslim mental health providers have incorporated  any spiritual or  Islamic dimension(s) into  their treatment or psychotherapy  since Malaysia and Indonesia have quite a number of Muslim psychiatrists and psychologists. The result showed that both of the Malaysian psychiatrists that we interviewed mentioned bipolar disorder as the disorder that they can easily misdiagnose.